2000
DOI: 10.3109/10425170009033969
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Analysis of Three Peroxide Sensor Regulatory Gene HomologsahpC, ahpXandoxyRinStreptomyces viridosporusT7A -A Lignocellulose Degrading Actinomycete

Abstract: Increased lignolytic peroxidase activity has been demonstrated with the addition of sublethal doses of toxic H2O2 in Streptomyces viridosporus T7A. Until now, the effect of H2O2 at the molecular level has not been well characterized. Here, for the first time we report the isolation and analysis of three peroxide-induced gene homologs from S. viridosporus T7A; ahpC and ahpX (encoding alkyl hydroxyperoxidase subunits) and oxyR (encoding oxygen stress regulatory protein). The genome organization of these stress r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The actinobacteria isolates grown on azure B media revealed their potential of producing lignin peroxidase (LiP) (Archibald 1992;Pangallo et al 2009). Ramachandran et al (2000) also found LiP in actinobacteria and observed increased activity in the presence of H 2 O 2 . Crawford (1978) reported that lignin from actinobacteria decayed softwood was extensively demethylated, distorted aromatic rings and undergone side-chain oxidation which were suggested to produce extracellular ligninolytic enzymes for breaking lignin barrier and exposed cellulose and hemicelluloses for further biodegradation.…”
Section: Resultsmentioning
confidence: 80%
“…The actinobacteria isolates grown on azure B media revealed their potential of producing lignin peroxidase (LiP) (Archibald 1992;Pangallo et al 2009). Ramachandran et al (2000) also found LiP in actinobacteria and observed increased activity in the presence of H 2 O 2 . Crawford (1978) reported that lignin from actinobacteria decayed softwood was extensively demethylated, distorted aromatic rings and undergone side-chain oxidation which were suggested to produce extracellular ligninolytic enzymes for breaking lignin barrier and exposed cellulose and hemicelluloses for further biodegradation.…”
Section: Resultsmentioning
confidence: 80%
“…KatA is under the control of OxyR in N. gonorrhoeae (Tseng et al ., 2003). The presence of both PerR and OxyR in a bacterium is extremely rare and apart from our observation in N. gonorrhoeae such a situation has only been described in Streptomyces coelicolor , which has OxyR and the H 2 O 2 ‐sensitive Fur‐like repressor, CatR (Hahn et al ., 2000; 2002), and Streptomyces viridosporus , which contains three peroxide sensor regulatory gene homologues ahpA , ahpX and oxyR (Ramachandran et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to its counterparts bacterial enzymology for lignin degradation was not well understood. According to Ramachandran et.al (2000), Streptococcus viridosporus T7A, a lignin degrading bacterium produces several extracellular peroxidases which are similar to the peroxidases produced by fungi 18 . Recent advancements in the genome sequencing studies reveal that laccases are also widespread in several bacterial strains 19 .…”
Section: Introductionmentioning
confidence: 99%